Implementation of the Sorogan Method in Improving the Ability to Read the Yellow Book ‘Kitab Kuning’ of Santri at the Sabilunnajah Islamic Boarding School - Muhammad Zainal Arifin (Journal of Contemporary Islamic Education, 2023)
In order to improve the skills of students in reading and to understand the yellow book, teachers always try to try various methods and strategies in learning, including using the sorogan. The culture in Islamic boarding schools with the sorogan method prioritizes solid emotional ties and intensive monitoring from the teacher to the students. This research is field research with data collection techniques using a combined technique (observation, questionnaire, interview, and documentation). Meanwhile, for data analysis, the writer used a qualitative approach. The purpose of this study was to determine the application of the sorogan method by the Sabilunnajah Islamic Boarding School to improve the ability to read the yellow book. Based on the results of data analysis in the discussion of this study, the sorogan method is one of the determining factors in success which plays an important role in increasing the ability to read the yellow book